Kunstcollectie Provincie Antwerpen - Van Kersschaever, Jasmina; Sonck, Jacques; Beerten, Katelijne; Lebeer, Griet; Limbos, Caroline (Antwerpen : Provinciebestuur Antwerpen, 2006)
't Jolle, Sven ; Aguirre y Otegui, Philip ; Albert, Ernest ; Baekelmans, Guy ; van Bergen, Thé ; Bervoets, Fred ; Bervoets, Leo ; De Beul, Bert ; Van Beurden, Alphonse ; Bijl, Guillaume ; van Boekhout, Hetty ; Van Bossche, Guy ; Van Breedam, Camiel ; van den Broek, Koen ; Broucke, Koen ; Brouwers, Rik ; De Bruyne, Gustaaf C. ; Bruyneel, Hans ; Bruyninckx, Robert ; Bury, Pol ; Cantre, Jan Frans ; Chapelle, Chantal ; Claerbout, David ; De Clerck, Sandra ; Cockx, Jan ; Cornelis, Beniti ; Cornelissen, Remy ; Cotteleer, Anton ; Cox, Jan ; Crabeels, Florent ; Creytens, Julien ; Crunelle, José ; Daems, Anne ; Daeye, Hippolyte ; Delahaut, Jo ; Delanghe, Rudie ; Deleu, Luc ; Denmark ; Van Dessel, Kris ; Devos, Danny ; Dillemans, Sam ; Dolphyn, Willem ; Dries, Jan ; Van Dromme, Robert ; Ducaju, Jozef Jaak ; Dupont, Veerle ; Van Dyck, Albert ; Eecken, Dirk Vander ; Ensor, James ; Everaet, Mieke ; Fabre, Jan ; Farasyn, Edgard ; Flips, George ; Francis, Filip ; Geefs, Willem ; Gentils, Frans ; Gentils, Paul ; Gentils, Vic ; Van Gestel, Fik ; Geys, Jef ; Ghekiere, Joris ; Godderis, Jack ; Goezu, André ; Goiris, Geert ; Goossens, Walter ; Guiette, René ; Hendrickx, Jos ; Heyrman, Hugo (Dr. Hugo Heyrman) ; Van Hoeydonck, Paul ; Huycke, David ; Huyghe, Philip ; Ibou, Paul ; Van Isacker, Philip ; Jacobs, Jacob ; Jespers, Floris ; Jespers, Oscar ; Joostens, Paul ; Van Kerckhoven, Anne-Mie ; De Keyser, Nicaise ; Kiemeneij, Jan ; Kokken, Henry ; Kreitz, Willy ; L'Anverre ; Lafontaine, Marie-Jo ; Langmans, Willy ; Leblanc, Walter ; Van Leemputten, Frans ; de Leeuw, Bert ; Leibovitz, Edward ; Leys, Henri ; Luyten, Mark ; Macken, Mark ; van Maele, Marcel ; Mara, Pol ; Mariën, Marcel ; Marstboom, Antoon ; Masereel, Frans ; Mazy, Marcel ; Meerbergen, Rudolf ; Mees, Guy ; etc.
boek